Household Decisions and the Gender Gap in Job Satisfaction - Christian Bredemeier; Patrick Ndlovu; Suncica Vujic; Roland Winkler (Institute of Labor Economics (IZA), 2024)
This paper offers a novel theoretical explanation for the gender gap in job satisfaction, where women typically report higher job satisfaction than men. We argue that rational family decisions can result in divergent job choices for women and men, leading to increased job satisfaction but lower earnings for women, even when their preferences and expectations align with those of men. We develop this explanation within a theoretical model of collective household decision-making that considers relative earnings disparities within households. We provide empirical evidence supporting our model's predictions utilizing survey and administrative data from Canada.
Keywords: D13; J28; J16; 330; job satisfaction; gender gap; households